Residential proximity to vines and risk of childhood embryonal tumours in France - GEOCAP case-control study, 2006–2013 - Awounou, Danielle; Mancini, Matthieu; Lacour, Brigitte; de Crouy-Chanel, Perrine; Aerts, Isabelle; Minard-Colin, Véronique; Schleiermacher, Gudrun; Verschuur, Arnauld; Guissou, Sandra; Desandes, Emmanuel; Guldner, Laurence; Clavel, Jacqueline; et al. (Environmental research, 2024)
Exposure to pesticides has been suggested as a potential risk factor for childhood embryonal tumour. The existing literature has mainly focused on parental occupational exposure and domestic use of pesticides, and is very limited for residential exposures to agricultural pesticides. The study aimed to test the hypothesis of an increased risk of embryonal tumour in children living close to viticultural plots, likely to be subject to frequent pesticide applications.BACKGROUNDExposure to pesticides has been suggested as a potential risk factor for childhood embryonal tumour. The existing literature has mainly focused on parental occupational exposure and domestic use of pesticides, and is very limited for residential exposures to agricultural pesticides. The study aimed to test the hypothesis of an increased risk of embryonal tumour in children living close to viticultural plots, likely to be subject to frequent pesticide applications.The study is part of the French national registry-based GEOCAP program. We included 2761 cases of neuroblastoma, retinoblastoma, Wilms tumour and rhabdomyosarcoma diagnosed before the age of 15 years in the 2006-2013 period, and 40,196 controls representative of the same age population during this period. Indicators of proximity to vines, the presence of vines and viticulture density within 1000 m of the geocoded addresses of residence, were evaluated combining three sources of data on agricultural land use in a geographic information system. We estimated odds ratios (ORs) and 95% confidence intervals (CIs) using unconditional logistic regressions and carried out several sensitivity analyses to test the stability of the results.METHODSThe study is part of the French national registry-based GEOCAP program. We included 2761 cases of neuroblastoma, retinoblastoma, Wilms tumour and rhabdomyosarcoma diagnosed before the age of 15 years in the 2006-2013 period, and 40,196 controls representative of the same age population during this period. Indicators of proximity to vines, the presence of vines and viticulture density within 1000 m of the geocoded addresses of residence, were evaluated combining three sources of data on agricultural land use in a geographic information system. We estimated odds ratios (ORs) and 95% confidence intervals (CIs) using unconditional logistic regressions and carried out several sensitivity analyses to test the stability of the results.Approximately 10% of the controls lived within 1000 m of vines, with regional variations ranging from <1% to 38%. We observed a 5% increase in the risk of neuroblastoma for a 10% increase in viticulture density (OR = 1.05, 95% CI: 0.98-1.13), with a regional heterogeneity. The indicators of proximity to vines were not associated with the other non-CNS embryonal tumours.RESULTSApproximately 10% of the controls lived within 1000 m of vines, with regional variations ranging from <1% to 38%. We observed a 5% increase in the risk of neuroblastoma for a 10% increase in viticulture density (OR = 1.05, 95% CI: 0.98-1.13), with a regional heterogeneity. The indicators of proximity to vines were not associated with the other non-CNS embryonal tumours.The study showed a slight increase in the risk of neuroblastoma in children living close to vines, suggesting that residential exposure to agricultural pesticides may be involved in the occurrence of these tumours.CONCLUSIONThe study showed a slight increase in the risk of neuroblastoma in children living close to vines, suggesting that residential exposure to agricultural pesticides may be involved in the occurrence of these tumours.